Restoration of miRNA-143 Expression Inhibits Growth and Migration of MKN-45 Gastric Cancer Cell Line - Nayer Hosseinahli; Tahereh Zeinali; Nasrin Hosseinahli; Leila Karimi; Dariush Shanehbandi; Behzad Mansoori; Ali Mohammadi; Tohid Kazemi; Khalil Hajiasgharzadeh; Behzad Baradaran (Tabriz University of Medical Sciences, 2022)
Purpose: Gastric cancer (GC) is one of the main causes of death from diseases, especially in developing countries. MicroRNAs (miRNAs) are important modulators of the messenger RNAs expression. Among these miRNAs, MiR-143 is a tumor suppressor miRNA and its irregular expression has been revealed in a diversity of malignancies such as GC. Methods: In this study, we have attempted to restore the miR-143 expression in MKN-45 cells by introducing pCMV-miR-143 plasmid vectors. The consequences of exogenous expression of miR-143 on cell proliferation and migration were assessed by MTT and scratch tests, respectively. In addition, the DAPI staining assay was applied for apoptosisquantification. Following miR-143 transfection, the changes in K-Ras, C-Myc, MMP9, Bax, Caspase-3, and Caspase-9 mRNA levels were assessed. Results: The results indicated that the enhanced expression of miR-143 had negative effects on MKN-45 cells proliferation and invasion. Moreover, decreased expressions of K-Ras, MMP9, and C-Myc and up-regulation of Bax, Caspase-3, and Caspase-9 as downstream targets of miR-143 were recognized. Conclusion: These experimental results indicate that reversing the miR-143 expression, by novel techniques, including miRNA replacement could be considered as an efficient approach to reduce cell survival and metastasis.